2016
DOI: 10.1155/2016/1869082
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-375 a Sensor of Glucotoxicity Is Altered in the Serum of Children with Newly Diagnosed Type 1 Diabetes

Abstract: Background. The use of miRNAs as biomarkers for Type 1 Diabetes (T1D) risk is attractive as T1D is usually diagnosed in front of acute symptoms. As miR-375 is highly expressed in the endocrine pancreas, we postulated that its circulating level might reflect beta cell alterations and might be altered in the blood of T1D patients recently diagnosed. Methods. Sera were obtained from 22 T1D children at onset of the disease, before subcutaneous insulin treatment, and from 10 nondiabetic pediatric controls. MiR-375 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 40 publications
1
62
0
1
Order By: Relevance
“…The control group was chosen from children who visited the British Columbia Children's Hospital endocrinology division and were found to be healthy, with normal variations in growth and puberty and no evidence of either autoimmune disease or diabetes following comprehensive outpatient assessment. We first sought to investigate whether miR-375, a miRNA that we reported to be increased in the circulation of prediabetic mice (6) and a miRNA reported to be lower in the sera of children with newly diagnosed T1D (13), was altered in the sera of children with recent onset of diabetes. Measurement of miR-375 levels with qRT-PCR indicated that miR-375 was not significantly different in the sera of children with recent onset of diabetes ( Figure 1A), prompting us to perform an unbiased miR-NA screen.…”
Section: Resultsmentioning
confidence: 99%
“…The control group was chosen from children who visited the British Columbia Children's Hospital endocrinology division and were found to be healthy, with normal variations in growth and puberty and no evidence of either autoimmune disease or diabetes following comprehensive outpatient assessment. We first sought to investigate whether miR-375, a miRNA that we reported to be increased in the circulation of prediabetic mice (6) and a miRNA reported to be lower in the sera of children with newly diagnosed T1D (13), was altered in the sera of children with recent onset of diabetes. Measurement of miR-375 levels with qRT-PCR indicated that miR-375 was not significantly different in the sera of children with recent onset of diabetes ( Figure 1A), prompting us to perform an unbiased miR-NA screen.…”
Section: Resultsmentioning
confidence: 99%
“…In the setting of type 1 diabetes, serum levels of miR-375, an islet cell miRNA, reflect beta cell destruction in mice [21] and islet transplant recipients [22], although this may be limited to acute damage and miR-375 is not exclusively of pancreatic beta cell origin. A few studies have reported perturbed serum miRNA levels in individuals with newly diagnosed type 1 diabetes compared with healthy participants [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…109 Interestingly, another study showed that the serum miR-375 level was lower in children with newly diagnosed T1D than in the age-matched control individuals. 110 Therefore, we speculated that a sudden increase in circulating miR-375 prior to T1D onset was likely to result from a pool of miR-375 immediately released during the process of β-cell death; in turn, this level will decrease after T1D onset, which may reflect β-cell residual functions.…”
Section: Mirnas: Participants In Autoimmunity-mediated β-Cell Damagementioning
confidence: 99%